The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1080/20518196.2021.1958615
|View full text |Cite
|
Sign up to set email alerts
|

Local voices on heritage: Understanding community perceptions towards archaeological sites in South Iraq

Abstract: Community engagement is now a consolidated and essential part of many archaeological research projects. In particular, it is widely recognized as a powerful tool for laying the foundation for any community archaeology programme. This paper explores the perceptions of a community living North-East of the city of Kufa (Iraq) towards the archaeological sites and cultural heritage in general. In particular, we designed an action-oriented research consisting of interviews and focus groups conducted between 2017 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…When we [young people] learn about our heritage, we do not just learn about it—we bring it to life and turn it into a better future. (Y7)A wide range of studies have investigated how the youth connect with heritage sites, such as their perception and valuing of archaeology (Zaina et al, 2021), heritage sites (McAra, 2021), engagement through museums (Tzibazi, 2013), digital platforms (Selim et al, 2022), social media, and local histories, memory, community, identity, and belonging (Benwell et al, 2020). Existing scholarship has demonstrated that engaging with heritage can positively affect individuals, communities, and societies, through acquiring skills, self-confidence, changing attitudes, creativity, cultural awareness, and cognitive abilities (Wavell et al, 2002).…”
Section: (Re)connecting the Youth With Heritagementioning
confidence: 99%
“…When we [young people] learn about our heritage, we do not just learn about it—we bring it to life and turn it into a better future. (Y7)A wide range of studies have investigated how the youth connect with heritage sites, such as their perception and valuing of archaeology (Zaina et al, 2021), heritage sites (McAra, 2021), engagement through museums (Tzibazi, 2013), digital platforms (Selim et al, 2022), social media, and local histories, memory, community, identity, and belonging (Benwell et al, 2020). Existing scholarship has demonstrated that engaging with heritage can positively affect individuals, communities, and societies, through acquiring skills, self-confidence, changing attitudes, creativity, cultural awareness, and cognitive abilities (Wavell et al, 2002).…”
Section: (Re)connecting the Youth With Heritagementioning
confidence: 99%